Targeting DNA Methylation and EZH2 Activity to Overcome Melanoma Resistance to Immunotherapy. Issue 4 (April 2019) - Emran, Abdullah Al; Chatterjee, Aniruddha; Rodger, Euan J.; Tiffen, Jessamy C.; Gallagher, Stuart J.; Eccles, Michael R.; Hersey, Peter
Abstract : Methylation of DNA at CpG sites is the most common and stable of epigenetic changes in cancer. Hypermethylation acts to limit immune checkpoint blockade immunotherapy by inhibiting endogenous interferon responses needed for recognition of cancer cells. By contrast, global hypomethylation results in the expression of programmed death ligand 1 (PD-L1) and inhibitory cytokines, accompanied by epithelial-mesenchymal changes that can contribute to immunosuppression. The drivers of these contrasting methylation states are not well understood. DNA methylation also plays a key role in cytotoxic T cell 'exhaustion' associated with tumor progression. We present an updated exploratory analysis of how DNA methylation may define patient subgroups and can be targeted to develop tailored treatment combinations to help improve patient outcomes. Highlights: Genome-wide DNA methylation is a relatively stable epigenetic characteristic of cells, which can be dysregulated in cancer cells by oncogenic signals. Hyper- or hypomethylation of DNA in melanoma cells underlies the categorization of melanoma patients into four groups according to PD-L1 expression and T cell infiltration. Resistance of melanoma to immunotherapy by immune checkpoint inhibitors is associated with global hypermethylation and low PD-L1 expression whereas global hypomethylation is associated with constitutive PD-L1 expression and inhibitory cytokine production. Hypermethylation of DNA in melanoma is associated with overexpression of DNA methyltransferases (DNMTs) and histone methyltransferase-EZH2 in the PRC2 repressive complex. The T cell exhaustion state is associated with hypomethylation of PD1, LAG3, and TIM3 promoters. EZH2 can be activated by the YY1 transcription factor in human melanoma cells, downregulating the IL2 promoter by de novo methylation.